An Era of Contactless Heart Monitoring - Tuhina Raj (International Journal of Medical Toxicology and Legal Medicine, 2024)
A non-invasive medical test called an electrocardiogram (ECG) is used to monitor the electrical signals of the heart. Electrodes must be placed to the skin for a conventional ECG, which can be uncomfortable and cumbersome for patients. The development of skin-free ECG devices that can monitor the heart is receiving increasing attention in recent years. This research considers contactless ECG technologies based on electromagnetic radiation and radar and offers broad comparisons based on several newly updated improved criteria. ECG technology provide several of possible benefits over conventional ECG. For patients, they are not disruptive and convenient. Technologies for contactless ECG monitoring are anticipated to be used more frequently in healthcare facilities as they develop. This technological change completely enhances the efficiency and usage for how we identify and track heart diseases, giving patients access to more precise, and more customized treatment. Technologies for contactless ECG monitoring are expected to be used more often in clinical settings as they progress. This research paper gathers the latest developments for the previously mentioned technologies, including cardiac monitoring, from multiple research studies. The assessment also covers the technology’s likely future applications and research challenges.